Enhanced grain growth and dielectric properties in aerosol deposited BaTiO3. Issue 10 (August 2023) - Bentzen, Marcus; Maier, Juliana; Eckstein, Udo; He, Jianying; Henss, Anja; Khansur, Neamul; Glaum, Julia
Abstract: Piezoelectric ceramics are envisioned as cell stimulating materials for in-vivo, load-bearing applications. To compensate for their brittle nature developing ceramic films on medically accredited metals is a promising approach. However, high temperature consolidation is often required to achieve highly dense ceramics with suitable functional properties, which can compromise the metal substrate integrity. With aerosol deposition highly dense thick films can be produced at room temperature. Still, an annealing step is required to enhance the functional properties of piezoelectric ceramics. Thermal annealing of dense, aerosol deposited BaTiO3 thick films on 304SUS stainless steel gave a clear enhancement of the dielectric properties. An increase in saturation polarization and the adoption of ferroelectric hysteresis at 750 °C coincided with a significant reduction in mechanical properties. The simultaneous appearance of grain growth and diffusion of chromium from the substrate at 750 °C suggests that chromium acts as a sintering aid. Graphical Abstract: ga1 Highlights: Thermal annealing results in transition from dielectric to ferroelectric polarization hysteresis behavior. Thermal expansion coefficient mismatch between film and substrate influence quality of annealed film. Correlation between grain-growth and chromium diffusion from substrate into thick film.